Mechanism of Hexagon Fraud Detection in Mitigating Fraudulent Financial Reporting - Zulqirofik, Tedy; Raharja, Surya (Dinasti Publisher, 2026)
This study aims to examine the effect of the fraud hexagon on fraudulent financial reporting at Regional Development Banks in Indonesia from 2019 to 2022. This research method uses a quantitative approach to examine the effect of independent variables on dependent variables. The research sample used a purposive method with a sample size of 104. The data source for this research was obtained from the ojk.go.id website. The data analysis method used was logistic regression in SPSS 26. The results of the research indicate that financial targets, financial stability, external pressure, ineffective monitoring, director in change, and government projects have a positive effect on fraudulent financial reporting. Meanwhile, the nature of the industry, auditor in change, CEO picture, and political connections have no effect on fraudulent financial reporting. The results of this study have implications for provincial governments in Indonesia to mitigate the risk of fraud in financial statements by considering factors that can influence fraudulent acts in the financial statements of Regional Development Banks.